Analisis Persepsi Mahasiswa terhadap Efektivitas Pembelajaran Kimia Secara Daring pada Masa Pandemi Covid 19 - Heni, Astrina; Sormin, Elferida; Purba, Leony Sanga Lamsari; Harefa, Nelius (Jurnal Pendidikan Impola, 2025)
This study aims to determine students' perceptions of the effectiveness of online chemistry learning during the Covid-19 pandemic. The study population was all students of the Chemistry Education Study Program, Faculty of Teacher Training and Education, Indonesian Christian University. The research sample was 47 students of the Chemistry Education Study Program at Indonesian Christian University, selected using the saturated sampling technique. The instrument used was a closed questionnaire about the perceptions of Chemistry Education students towards online learning which was compiled using the Likert scale method, consisting of three indicators, namely, acceptance, understanding, and evaluation. The research data were analyzed using descriptive statistics. The results of the study showed that students' perceptions of online chemistry learning during the Covid-19 pandemic for the acceptance indicator were 75.38% in the good category, the understanding indicator was 72.19% in the good category, and the evaluation indicator was 70.26% in the good category. When generalized, students' perceptions of online chemistry learning averaged 72.61% in the good category. Thus, the implementation of online learning during the Covid 19 pandemic went well and students thought that the facilities provided could support learning well.